Інтертекстуальні одиниці у прозі Юрія Іздрика - Назаренко, О. (Культура слова, 2019)
Статтю присвячено дослідженню сучасної української прози Ю. Іздрика в аспекті реалізації категорії інтертекстуальності. Простежено різновиди інтертекстуальних одиниць у прозових текстах Юрія Іздрика: ремінісценції, парафрази, алюзії, цитати (паспортизовані й не паспортизовані). Доведено, що інтертекстуальність – це диференційна категорія постмодерністської прози, а інтертекстеми виконують текстотвірну функцію. Запропоновано типологію інтертекстуальних елементів у художньому прозовому тексті. The article is devoted to the study of the implementation of the category of intertextuality in modern Ukrainian prose by Yu. Izdryk. An excursion into the theory of intertextuality presented in modern linguistics is made. Intertextual elements in the literary text are updated and their sources are determined. Two types of intertext in modern prose are distinguished depending on the source. The first type includes intertextual elements, the sources of which are works of literature. Among them: allusions, quotes (certified and non-certified), reminiscences, paraphrases, parades on literary texts by Ukrainian classical authors, memoirs of ancient Ukrainian literature, in particular, “The Tale of Igor’s Campaign”, works by contemporary postmodern writers. The second group of intertextual units is connected with texts of mass culture – the names of films, quotes from films, pop songs and quotes from them, allusions to cartoons. The work of Yu. Izdryk is designed for an educated reader who is able to recognize a complex of intertextual elements. It is proved that intertextuality is the main category of postmodern prose and performs a text-forming function.